(untitled) (Journal of Universal Science Research, 2025)
Neuroblastoma is among the most common malignancies in the pediatric population. The disease is often difficult to diagnose in its early stages, highlighting the need for advanced and effective treatment strategies. Neuroblastoma is one of the most extensively studied tumors in pediatric oncology, offering opportunities to improve outcomes and quality of life for affected children. Objective: To investigate the pathogenesis of neuroblastoma in children, with a focus on identifying key cellular, genetic, and molecular abnormalities underlying tumor development.